Maternal, fetal and neonatal heart rate and heart rate variability in Holstein cattle - Quevedo, Dario A.C.; Lourenço, Maria Lucia G. [UNESP]; Bolaños, Carmen D. [UNESP]; Alfonso, Angélica [UNESP]; Ulian, Carla M.V. [UNESP]; Chiacchio, Simone B. [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to describe the normal values for maternal, fetal and neonatal heart rate (HR) and heart rate variability (HRV) indexes in the time domain (standard deviation of beat-to-beat interval- SDNN; root mean square of successive beat-to-beat differences- RMSSD) and the frequency domain (low frequency- LF; high frequency- HF; relationship between low and high frequency- LF/HF) in 23 Holstein cows, 23 fetuses and 18 neonates during the perinatal period. HR and HRV were calculated by fetomaternal electrocardiography (ECG). Fetomaternal measurements were taken six times prepartum (between days 234 and 279 of pregnancy) and measurements were taken in neonates six times after calving (after birth and five times weekly). HR, time and frequency domain were analyzed. No significant changes in maternal, fetal beat-to-beat interval (RR interval) or HR were found. In maternal variables, SDNN decreased significantly from 38.08±2.6ms (day 14 before calving) to 23.7±2.5ms (day 1 after calving) (p<0.05), but the RMSSD did not change significantly. HR and RR interval of calf differed statistically from the day before delivery (163±7.5bpm; 381±24.2ms) to the day after calving (131±5bpm; 472±16.2ms). Time variables (SDNN and RMSSD) and the frequency-domain variables (LF and HF) were significantly different (p<0.05) between fetal and neonatal stages. Reductions in the values of SDNN and RMSSD can reflect a sympathetic dominance. After calving, the increase in HF and decrease in LF variables can indicate activation of the vagal nerve followed by heart and respiratory modulation.